Linking macroscopic rejuvenation to nano-elastic fluctuations in a metallic glass. (1st October 2017) - Ross, Perry; Küchemann, Stefan; Derlet, Peter M.; Yu, HaiBin; Arnold, Walter; Liaw, Peter; Samwer, Konrad; Maaß, Robert
Abstract: Metallic glasses are structurally heterogeneous below a certain length scale. Here we demonstrate how elastic heterogeneities change in response to a macroscopic cyclic, but elastic, loading protocol. Fluctuations in local elastic properties are spatially resolved across the surface of a bulk sample by evaluating nano-scale contact resonances of an atomic force microscope. The findings indicate a significant increase in nano-elastic fluctuations due to loading. The distribution of these fluctuations broadens symmetrically and almost three fold, revealing how the atomically disordered structure is driven further out of equilibrium at the nano-scale. Macroscopically, the stress-driven elastic heterogeneities lead to a rejuvenation and therefore a new structural state of the bulk metallic glass, characterized by a higher energy release during heating and mechanical softening. These results show how macroscopic energy storage in metallic glasses may be linked to the development of nano-scale elastic fluctuations. Graphical abstract: Image